English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

By completing the Square we can change any quadratic function of the form y=ax^+bx+c into a quadratic function in vertex form

2007-01-11 06:44:33 · 4 answers · asked by haileybaby331 1 in Science & Mathematics Mathematics

4 answers

true
y = ax^2 + bx + c
y = a(x^2 + (b/a)x + c/a)
y = a(x^2 + (b/a)x + (b/2a)^2 - (b/2a)^2 + c/a)
y = a(x + b/2a)^2 - a(b/2a)^2 + c
y + a(b/2a)^2 - c = a(x + b/2a)^2
(y + b^2/4a - c) = a(x + b/2a)^2

2007-01-11 07:07:59 · answer #1 · answered by Helmut 7 · 0 0

false

2007-01-11 15:00:01 · answer #2 · answered by parrotsarenoisy 5 · 0 0

false...... i think

2007-01-11 14:52:16 · answer #3 · answered by Dazza 2 · 0 0

true.. i am sure.

2007-01-11 14:54:36 · answer #4 · answered by jackie 1 · 0 0

fedest.com, questions and answers